Sacrifice of Involved Nerve Root during Surgical Resection of Foraminal and/or Dumbbell Spinal Neurinomas - Alberto Vandenbulcke; Ginevra Federica D’Onofrio; Gabriele Capo; Wassim Baassiri; Cédric Y. Barrey (Brain Sciences, 2023)
Even if usually needed to achieve the gross total resection (GTR) of spinal benign nerve sheath tumors (NSTs), nerve root sacrifice remains controversial regarding the risk of neurological deficit. For foraminal NSTs, we hypothesize that the involved root is poorly functional and thus can be safely sacrificed. All spinal benign NSTs with foraminal extension that underwent surgery from 2013 to 2021 were reviewed. The impacts of preoperative clinical status and patient and tumor characteristics on long-term outcomes were analyzed. Twenty-six patients were included, with a mean follow-up (FU) of 22.4 months. Functional motor roots (C5-T1, L3-S1) were involved in 14 cases. The involved nerve root was routinely sacrificed during surgery and GTR was obtained in 84.6% of cases. In the functional root subgroup, for patients with a pre-existing deficit (n = 5/14), neurological aggravation persisted in one case at last FU (n = 1/5), whereas for those with no preop deficit (n = 9/14), a postoperative deficit persisted in one patient only (n = 1/9). Preoperative radicular pain was the only characteristic significantly associated with an immediate postoperative motor deficit (p = 0.03). The sacrifice of an involved nerve root in foraminal NSTs seems to represent a reasonable and relevant option to resect these tumors, permitting one to achieve tumor resection in an oncologic fashion with a high rate of GTR.